Factors influencing the actual usage of e-government among employees within public sector organizations in the UAE - Kamalrudin, Massila; Alzarooni, Abdalla Jafar Mohamed Abbas; Akmal, Suriati; Jaber, Mustafa Musa (International journal of health sciences, 2022)
Organizations are becoming flatter, more flexible and networked due to the advent of new technologies. Leaders in the United Arab Emirates (UAE) aim to be attain the first spot worldwide in terms of efficiency and effectiveness by focusing on long- term vision and strategy. However, the gap between the essential indicators of ICT towards UAE’s government vision might affect the long-term goals. This study addresses the relationship between smart government effectiveness and knowledge management, while considering the role of institutional challenges as a moderator variable within the public sector in UAE. As a guide for the proposed model in this study, three acceptance models were implemented, namely, the unified theory of acceptance and use of technology (UTAUT), technology acceptance model (TAM), and DeLone and McLean model of information systems success (D&M IS Success Model) as guided for the proposed model. Additionally, quantitative data were collected in this study and analyzed using the Statistical Package for Social Science (SPSS) and Smarts software. Resultantly, the actual use of E-government was predicted and significantly associated with the change in “Influencing factors”, comprising system quality, information quality, service quality, and social influence. In conclusion, the research hypotheses were accepted as the findings revealed a statistical relationship between the actual use of E-government and influencing factors.